The Role of Recreational Sports in Enhancing the Self from a Psychomotor Side for Mentally Retarded People. (But able to learn) - Rahli , Mourad; Saoudi , Djenidi (sports creativity, 2025)
The primary goal of this study to know The Role of Recreational Sports in Enhancing the Self from a Psychomotor Side for Mentally Retarded People , we used as a tool for the stady of the questionnaire on the sample represented in 17 Teacher , The results are as follows : -Recreational sports contribute to the acquisition of both a physical competence and good health for this group - Recreational sports have a great contribution to improving the psychological side of this group. -Recreational sports decrease psychological disorders. -Recreational sports give one the feeling of safety and happiness. -Recreational sports contribute to satisfying some psychological needs and also proving oneself